2021
DOI: 10.1093/nar/gkab125
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric complexes formed by Redβ single strand annealing protein in its different DNA bound states

Abstract: Redβ is a single strand annealing protein from bacteriophage λ that binds loosely to ssDNA, not at all to pre-formed dsDNA, but tightly to a duplex intermediate of annealing. As viewed by electron microscopy, Redβ forms oligomeric rings on ssDNA substrate, and helical filaments on the annealed duplex intermediate. However, it is not clear if these are the functional forms of the protein in vivo. We have used size-exclusion chromatography coupled with multi-angle light scattering, analytical ultracentrifugation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…4). Based on our previous results for λ-Redβ (17), we interpret the smaller complexes (green) as initial LiRecT-ssDNA substrate complexes, and the larger complexes (blue) as attempts at annealing at sites of partial complementarity. By contrast, mixing of LiRecT with the two complementary 83-mers added sequentially resulted in a more dominant complex containing 17 or 18 copies of LiRecT and one copy each of the 83+ and 83-oligonucleotides (purple in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…4). Based on our previous results for λ-Redβ (17), we interpret the smaller complexes (green) as initial LiRecT-ssDNA substrate complexes, and the larger complexes (blue) as attempts at annealing at sites of partial complementarity. By contrast, mixing of LiRecT with the two complementary 83-mers added sequentially resulted in a more dominant complex containing 17 or 18 copies of LiRecT and one copy each of the 83+ and 83-oligonucleotides (purple in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Our experiment was limited to 10 μM Redβ, whereas Matsubara et al tested Redβ concentrations as high as 100 μM. Although prior studies indicated that the concentration of Redβ in cells active for recombination is lower than 150 nM [ 39 ], we have recently re-examined the in vivo concentration of Redβ in two different expression systems commonly used for recombineering and found it to range from 7 to 27 μM [ 40 ]. With regard to DNA annealing, both studies used 50-mer oligonucleotides to assess the formation of the complex with annealed duplex.…”
Section: Discussionmentioning
confidence: 99%
“…We used a single concentration of Redβ instead of a titration as due to the sequential addition of complementary oligonucleotides, as well as the lack of binding of Redβ to pre-formed dsDNA, this experiment is not an equilibrium measurement, and thus a meaningful binding affinity cannot be obtained. Furthermore, we have recently demonstrated that formation of the complex with annealed duplex is not sensitive to ionic strength or buffer composition and does not require added Mg 2+ ion [ 40 ]. Nonetheless, we consider measurements at physiological ionic strength to be most meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Many studies have exploited ESI-MS as a means to preserve and facilitate analysis of native interactions, including DNA-small molecule ligand complexes, [20][21][22][23] DNA-templated silver clusters, [24][25][26][27] DNA duplex and quadruplex complexes, [28][29][30] and protein-DNA complexes. [31][32][33][34][35][36][37][38][39] Native ESI-MS studies of DNA complexes have enabled the determination of DNA-ligand stoichiometry, 32,38 ligand selectivity, 21 and DNA-binding pathways. 35 Analyses of native complexes such as these are contingent upon the exceptional performance of high-resolution and high-mass accuracy mass spectrometers.…”
Section: Introductionmentioning
confidence: 99%
“…41 In general, compared to ESI-MS of multiprotein complexes, fewer studies have reported the analysis of protein-DNA complexes. [31][32][33][34][35][36][37][38][39] Analysis of protein-nucleic acid complexes containing large DNA or RNA strands (>20 nucleotides) in positive-ion mode typically generates spectra that are complicated by the presence of highly heterogeneous ion populations arising from cation adduction. 42 However, the addition of volatile salts (e.g., ammonium acetate) minimizes the prevalence of cation adduction for protein-DNA complexes.…”
Section: Introductionmentioning
confidence: 99%